Proceedings of the International Conference on Data Engineering and Communication Technology ICDECT 2016, Volume 2 - Satapathy, Suresh Chandra; Bhateja, Vikrant; Joshi, Amit.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This two-volume book contains research work presented at the First International Conference on Data Engineering and Communication Technology (ICDECT) held during March 10-11, 2016 at Lavasa, Pune, Maharashtra, India. The book discusses recent research technologies and applications in the field of Computer Science, Electrical and Electronics Engineering. The aim of the Proceedings is to provide cutting-edge developments taking place in the field data engineering and communication technologies which will assist the researchers and practitioners from both academia as well as industry to advance their field of study.
Chapter 1. Experimental Analysis on Big Data in IOT based Architecture -- Chapter 2. Morphology Based Approach for Number Plate Extraction -- Chapter 3. NeSeDroid - Android Malware Detection Based on Network Traffic and Sensitive Resource Accessing -- Chapter 4. RiCoBiT - Ring Connected Binary Tree: A Structured and Scalable Architecture for Network on Chip Based Systems: An Exclusive Summary -- Chapter 5. Application of Compressed Sensing (CS) for ECG Signal Compression: A Review -- Chapter 6. Tracking Pointer Based Approach for Iceberg Query Evaluation -- Chapter 7. Performance Evaluation of Shortest Path Routing Algorithms in Real-road Networks -- Chapter 8. An Outlook in Some Aspects of Hybrid Decision Tree Classification Approach: A Survey -- Chapter 9. Content Search Quaternary Look-up Table Architecture -- Chapter 10. Exhaust Gas Emission Analysis of Automotive Vehicles Using FPGA -- Chapter 11. A Graph BasedActive Learning Approach Using Forest Classifier for Image Retrieval -- Chapter 12. Comparative Analysis of Android Malware Detection Techniques -- Chapter 13. Developing Secure Cloud Storage System by Using Access Control Models -- Chapter 14. ETLR - Effective DWH Design Paradigm -- Chapter 15. Prediction of Reactor Performance in CATSOL Based Sulphur Recovery Unit by ANN -- Chapter 16. A Multilevel Clustering Using Multi-hop and Multi-head in VANET -- Chapter 17. Patient-speci Cardiac Computational Modeling Based on Left Ventricle Segmentation from Magnetic Resonance Images -- Chapter 18. A Cryptographic Key Generation on a 2D Graphics Using RGB Pixel Shuffling and Transposition -- Chapter 19. Methods for Individual and Group Decision Making Using Interval Valued Fuzzy Preference Relations -- Chapter 20. A New Approach to Determine Tie Line Frequency Bias (B) in Interconnected Power System with Integral Control AGC Scheme -- Chapter 21. Significance of Frequency Band Selection of MFCC for Text-independent Speaker Identification -- Chapter 22. Ensuring Performance of Graphics Processing Units: A Programmer's Perspective -- Chapter 23. Analytical Study of Miniaturization of Microstrip Antenna for Bluetooth/WiMax -- Chapter 24. Novel All Optical Encoding and Decoding Scheme for Code Preservation -- Chapter 25. XPM BASED Bandwidth Efficient WDM-to-OTDM Conversion Using HNLF -- Chapter 26. Analysis of a Sporting Event on a Social Network: True Popularity & Popularity Bond -- Chapter 27. Performance Analysis of LPC and MFCC Features in Voice Conversion using Artificial Neural Networks -- Chapter 28. Person Detection & Tracking Using Sparse Matrix Measurement for Visual Surveillance -- Chapter 29. Improvisation in Frequent Pattern Mining Technique -- Chapter 30. Design and Simulation of Hybrid SETMOS Operator Using Multiple Value Logic at 120nm Technology -- Chapter 31. Detailed Survey on Attacks in Wireless Sensor Network -- Chapter 32. Comparative Analysis of Frontal Face Recognition Using Radial Curves and Back Propagation Neural Network -- Chapter 33. Data Perturbation: An Approach to Protect Confidential Data in Cloud Environment -- Chapter 34. Biologically Inspired Techniques for Cognitive Decision-Making -- Chapter 35. Analysis of Edge Detection Techniques for Side Scan Sonar Image Using Block Processing and Fuzzy Logic Methods -- Chapter 36. Leveraging Virtualization for Optimal Resource Management in a Cloud Environment -- Chapter 37. Reconfigurable Circular Microstrip Patch Antenna With Polarization Diversity -- Chapter 38. Issues with DCR and NLSR in Named Based Routing Protocol -- Chapter 39. Design and Analysis of Quantum Dot Cellular Automata Technology based Reversible Multifunction Block -- Chapter 40. Text Independent Automatic Accent Identification Systemfor Kannada Language -- Chapter 41. Study The Effect of Adaptive Boosting on Performance of Classifiers for Human Activity Recognition -- Chapter 42. Towards Improved performance of emotion detection: Multimodal approach -- Chapter 43. Priority Dissection Supervision for Intrusion Detection in Wireless Sensor Networks -- Chapter 44. Multi-Objective Evolution based Scheduling of Computational Intensive Applications in Grid Environment -- Chapter 45. Selective Encryption Framework For Secure Multimedia Transmission Over Wireless Multimedia Sensor Networks -- Chapter 46. Mining Frequent Quality Factors of Software System using Apriori Algorithm -- Chapter 47. Algorithm for the Enumeration and Identification of Kinematic Chains -- Chapter 48. A New Congestion Avoidance and Mitigation Mechanism based on Traffic Assignment Factor and Transit Routing in MANET -- Chapter 49. MRWDPP: Multipath Routing Wormhole Detection and Prevention Protocol in Mobile Ad Hoc Networks -- Chapter 50. Self-coordinating bus route system to avoid bus bunching -- Chapter 51. Review on Data Hiding In Motion Vectors and in Intra prediction modes for video compression -- Chapter 52. Generation of Product Cipher for Secure Encryption and Decryption based on Vedic Encryption Ideology and using Variable and Multiple Keys -- Chapter 53. A Novel Integer Representation Based Approach for Classification of Text Documents -- Chapter 54. Communication Device for Differently-abled people: A Prototype Model -- Chapter 55. Combination of PCA and Contourlets for Multispectral Image Fusion -- Chapter 56. A Behavioral Study of Some Widely Employed Partitional and Model-Based Clustering Algorithms and their Hybridizations -- Chapter 57. An Adaptive MapReduce Scheduler for Scalable Heterogeneous Systems -- Chapter 58. Enhancement In Connectivity By Distributed Beamforming In WSN -- Chapter 59. Sparse Representation Based Query Classification using LDA Topic Modeling -- Chapter 60. MULTIPLE HOME AUTOMATION ON RASPBERRY PI -- Chapter 61. Sentiment Analysis based on A.I. over Big Data -- Chapter 62. Negotiation and Monitoring of Service Level Agreements in cloud computing Services -- Chapter 63. IMPACT OF PERFORMANCE MANAGEMENT PROCESS ON PRINT ORGANIZATIONAL PERFORMANCE- IN INDIAN CONTEXT -- Chapter 64. Mobility Aware Path Discovery for efficient routing in Wireless Multimedia Sensor Network -- Chapter 65. Emerging Internet of Things in Revolutionizing Healthcare -- Chapter 66. Swarm Intelligent WSN for Smart City -- Chapter 67. Representing natural language Sentences in RDF graphs to derive Knowledge Patterns -- Chapter 68. A Framework to Enhance Security for OTP SMS in E-Banking Environment using Cryptography and Text Steganography -- Chapter 69. Study on the use of Geographic Information System (GIS) for Effective Transport Planning for Transport for London (TfL) -- Chapter 70. AN INTEGRATION OF BIG DATA AND CLOUD COMPUTING -- Chapter 71. A New Approach for Fast Transmission to Remote Cooperative Groups with a New Key Paradigm using Voice Authentication -- Chapter 72. ICT enabled proposed solutions for Soil Fertility Management in Indian Agriculture -- Chapter 73. Software Maintenance: From the Perspective of Effort and Cost Requirement -- Chapter 74. FPGA IMPLEMENTATION OF LOW POWER PIPELINED 32-BIT RISC PROCESSOR USING CLOCK GATING -- Chapter 75. Dynamic Software Aging Detection Based Fault Tolerant Software Rejuvenation Model for Virtualized Environment -- Chapter 76. Analysis of Group Performance by Swarm Agents in SACA Architecture -- Chapter 77. Background Modeling and Foreground Object Detection for Indoor Video Sequence -- Chapter 78. Agri-Guide: An Integrated Approach for Plant Disease Precaution, Detection & Treatment -- Chapter 79. <Determination of Area Change in Water Bodies and Vegetation for Geological Applications by using Temporal Satellite Images of IRS 1C/1D -- Chapter 80. Significance of Independent Component Analysis (ICA) for Epileptic Seizure Detection Using EEG Signals.
Keywords: Computational intelligence; Telecommunication; Artificial intelligence; Data protection; Computational Intelligence; Communications Engineering, Networks; Artificial Intelligence; Data and Information Security